Intellectual Giftedness and Psychopathology in Children and Adolescents: A Systematic Literature Review. (April 2016) - Francis, Rosanna; Hawes, David J.; Abbott, Maree
Using a systematic search strategy in which intellectual giftedness was operationalized in terms of IQ score, the authors examined evidence from studies reporting on associations between this aspect of giftedness and psychopathology. A total of 18 studies met the inclusion criteria: compared gifted (IQ ≥ 125) and nongifted (IQ = 90–110) peers or used IQ as a continuous variable (IQ = 90–125+) and used empirically validated psychopathology measures. Overall, results indicated that gifted children demonstrate superior socio-emotional adjustment and fewer behavioral difficulties than their typically developing peers. Issues that may bias the findings in this direction are highlighted, including the tendency to select participants from gifted programs. Some socio-emotional and behavioral difficulties associated with giftedness were found when dimensions such as levels of giftedness and ethnicity were considered. Recommendations for future research include the use of adequate sample size, longitudinal studies, individually administered cognitive abilities tests, and specific age-appropriate psychopathology measures; and testing interaction effects between variables, such as age, ethnicity, and gender.